Enhancement of seminal stains using background correction algorithm with colour filters. (June 2016) - Lee, Wee Chuen; Khoo, Bee Ee; Abdullah, Ahmad Fahmi Lim
Highlights: No image processing has been applied on seminal stains in literature. A new background correction algorithm (BCA) for seminal stains is proposed. Processing on two seminal stains images: with and without colour filters. Significant improvement on the detectable dilution after applying our BCA. This approach is simpler and cheaper than utilizing band-pass filters for BCA. Abstract: Evidence in crime scenes available in the form of biological stains which cannot be visualized during naked eye examination can be detected by imaging their fluorescence using a combination of excitation lights and suitable filters. These combinations selectively allow the passage of fluorescence light emitted from the targeted stains. However, interference from the fluorescence generated by many of the surface materials bearing the stains often renders it difficult to visualize the stains during forensic photography. This report describes the use of background correction algorithm (BCA) to enhance the visibility of seminal stain, a biological evidence that fluoresces. While earlier reports described the use of narrow band-pass filters for other fluorescing evidences, here, we utilize BCA to enhance images captured using commonly available colour filters, yellow, orange and red. Mean-based contrast adjustment was incorporated into BCA to adjust the background brightness for achieving similarity of images' background appearance, a crucial step for ensuring success while implementing BCA. Experiment results demonstrated the effectiveness of our proposed colour filters' approach using the improved BCA in enhancing the visibility of seminal stains in varying dilutions on selected surfaces.